Leucocyte count in children with complicated and uncomplicated acute appendicitis: a comparative study - Joseph, Liya (International Surgery Journal, 2019)
Background: Identification of complicated and uncomplicated acute appendicitis is important in children. In acute appendicitis, along with clinical evaluation and staging, many laboratory tests have been used. The aim of the study was to compare total leucocyte count in children with uncomplicated and complicated acute appendicitis in different age groups. Methods: Retrospective cohort study was performed in children who underwent appendicectomy, in a Government tertiary care institution between January 2017 and December 2018. 206 patients were divided into complicated and uncomplicated appendicitis. Total leucocyte count at time of admission was compared according to age. Unpaired t test and Chi-square test were used for statistical analysis. Results: There were 136 males and 70 females. 107 patients (51.94%) had complicated and 99 (48.06%) had uncomplicated appendicitis. Mean leucocyte count per µl in uncomplicated appendicitis was 18993±3540 in <5 years, 17155±3386 in 5-10 years and 15833±3613 in 10-15 years. The mean leucocyte count for complicated appendicitis was 19974±3658 in <5 years, 17727±4487 in 5-10 years and 17220±3411 in 10-15 years age group. In 10-15 years group, patients with complicated acute appendicitis had statistically significant higher values of mean total leucocyte count. Conclusions: Total leucocyte count can be used as marker of severity of acute appendicitis in children older than 10 years. In children with clinical suspicion of acute appendicitis, total leucocyte count >20000 per µl signifies complicated appendicitis in all age groups.